A new approach to medical image stitching using minimum average correlation energy filter and peak to side-lobe ratio - Salbiah, S.; Somaya, A.; Arof, Hamzah; Saleh, Z.S.; Ibrahim, Fatimah (Wiley, 2012)
Standard X-ray images using conventional screen-film technique have a limited field of view and failed to visualize the entire long bone on a single image. To produce images with whole body parts, digitized images from the films that contain portions of the body parts are assembled using image stitching. This article presents a new medical image stitching method that uses minimum average correlation energy filters to identify and merge pairs of X-ray medical images. The effectiveness of the proposed method is demonstrated in the experiments involving two databases that contain a total of 40 pairs of overlapping and nonoverlapping images. Then the experimental results are compared to those of the normalized cross correlation (NCC) method. It is found that the proposed method outperforms the NCC method in identifying both the overlapping and nonoverlapping medical images. The efficacy of the proposed method is further vindicated by its average execution time which is about five times shorter than that of the NCC method. Â© 2012 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 22, 166-171, 2012 Copyright Â© 2012 Wiley Periodicals, Inc.